PENGARUH INDEKS PEMBANGUNAN MANUSIA, TINGKAT PENGANGGURAN TERBUKA, PDRB, DAN PARTISIPASI ANGKATAN KERJA TERHADAP KEMISKINAN DI JAWA TENGAH TAHUN 2017-2022 - Andini, Anggun; Az Zakiyyah, Nurul Azizah (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Poverty, which is still a challenge in Central Java, has a worrying impact on various aspects of people's lives. This research aims to determine the influence of the Human Development Index (HDI), Open Unemployment Rate (TPT), Gross Regional Domestic Product (GRDP), and Labor Force Participation (PAK) on the poverty level in each district/city. in Central Java. The research method used is the use of panel data (time series and cross section) in 35 districts/cities in Central Java during the 2017-2022 period, by applying the Random Effect Model (REM). Research findings show that the Human Development Index (HDI) has a significant negative impact on poverty levels. On the other hand, the Open Unemployment Rate (TPT) has a positive and significant effect on the poverty level, while the Gross Regional Domestic Product (GRDP) makes a negative and significant contribution. However, Labor Force Participation (PAK) has not been proven to have a significant influence on poverty levels in districts/cities in Central Java.